2006
DOI: 10.1097/01.pas.0000213277.45715.82
|View full text |Cite
|
Sign up to set email alerts
|

Renal Cell Carcinoma Associated With Prominent Angioleiomyoma-like Proliferation

Abstract: Five cases of renal cell carcinoma of clear cell type are presented, Fuhrmann's grade 2, associated with a peculiar stromal proliferation having angioleiomyoma-like features. This proliferation was particularly prominent at the interphase between the tumor edge and the surrounding normal tissues, in which it acquired the configuration of a tumor capsule. Four similar cases were taken from the literature. We postulate that this angioleiomyoma-like change is a tumor epiphenomenon and that it represents yet anoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
60
3
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 17 publications
6
60
3
2
Order By: Relevance
“…113 Four similar cases had been previously reported in which angioleiomyoma-like stroma was admixed with clear cells that were interpreted as being either renal cell carcinoma or benign. [114][115][116][117] Since the publication of the original series two further reports have detailed the features of a further six cases.…”
Section: Leiomyomatous Renal Cell Carcinomamentioning
confidence: 82%
“…113 Four similar cases had been previously reported in which angioleiomyoma-like stroma was admixed with clear cells that were interpreted as being either renal cell carcinoma or benign. [114][115][116][117] Since the publication of the original series two further reports have detailed the features of a further six cases.…”
Section: Leiomyomatous Renal Cell Carcinomamentioning
confidence: 82%
“…21,22 As another point of differentiation, losses of chromosome 3 and 3p have been demonstrated in at least a subset of these tumors. 22 Michal et al 23 similarly reported the 'renal angiomyoadenomatous tumor,' which has subsequently been studied by other authors.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] However, the relationship of these tumors to other renal epithelial neoplasms, particularly clear cell renal cell carcinoma 4 and clear cell papillary renal cell carcinoma, 5-11 is incompletely understood. 13 To shed light on these relationships, in this study we assessed clinicopathological, immunohistochemical, and molecular features of renal epithelial neoplasms with a prominent stromal smooth muscle component.…”
Section: Discussionmentioning
confidence: 99%
“…Within the kidney, this proliferation also commonly entrapped non-neoplastic renal elements. 2 In some cases, entrapped non-neoplastic tubules became dilated, resembling cystic nephroma or mixed epithelial and stromal tumor. A prominent smooth muscle-like component was uniformly present as the basis for inclusion in this study; however, other areas of the stroma were edematous or hyalinized.…”
Section: Discussionmentioning
confidence: 99%